PENGARUH MAKET (TIRUAN 3 DIMENSI) TERHADAP KEMAMPUAN MEMBACA PETUNJUK DENAH PADA KELAS 4 SDN KARANGJAYA 01 KECAMATAN PEBAYURAN KABUPATEN BEKASI - Sholeh, Abdul; Kusuma, Dewi; Hilyatunnisa, Hilyatunnisa (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Abstract: This research is motivated by the low ability to read floor plan instructions of fourth-grade students of SDN Karangjaya 01, Pebayuran District, Bekasi Regency. Students experience difficulties in navigating roads, understanding cardinal directions, determining locations, and interpreting symbols so that learning outcomes have not reached the Minimum Competency (KKM). This study aims to determine the effect of models (three-dimensional replicas) on floor plan reading abilities. This study uses a quantitative approach with a one-group pretest–posttest design. The subjects of the study were 30 fourth-grade students who were selected using a saturated sampling technique. The instrument used was a multiple-choice test whose validity and reliability have been tested. Data analysis used normality tests, homogeneity tests, paired sample t-tests, and N-Gain tests. The results showed that the average pretest score of 68.97 increased to 80.93 in the posttest, with a calculated t-value of 21.364 > t-table 2.042 (Sig. 0.000 < 0.05) and an N-Gain of 0.4629, categorized as moderate. Thus, mock-ups have a positive and significant effect on students' ability to read floor plan instructions. Keywords: Maket, Reading Floor Plan Instructions, Quantitative Abstrak: Penelitian ini dilatarbelakangi oleh rendahnya kemampuan membaca petunjuk denah peserta didik kelas IV SDN Karangjaya 01 Kecamatan Pebayuran Kabupaten Bekasi. Peserta didik mengalami kesulitan menelusuri jalan, memahami arah mata angin, menentukan lokasi, dan menafsirkan simbol sehingga hasil belajar belum mencapai KKM. Penelitian ini bertujuan mengetahui pengaruh media maket (tiruan tiga dimensi) terhadap kemampuan membaca denah. Penelitian menggunakan pendekatan kuantitatif dengan desain one group pretest–posttest. Subjek berjumlah 30 peserta didik kelas IV yang diambil dengan teknik sampling jenuh. Instrumen berupa tes pilihan ganda yang diuji validitas dan reliabilitasnya. Analisis data menggunakan uji normalitas, homogenitas, paired sample t-test, dan N-Gain. Hasil penelitian menunjukkan rata-rata nilai pretest 68,97 meningkat menjadi 80,93 pada posttest dengan thitung 21,364 > ttabel 2,042 (Sig. 0,000 < 0,05) serta N-Gain 0,4629 kategori sedang. Dengan demikian, maket berpengaruh positif dan signifikan terhadap kemampuan membaca petunjuk denah peserta didik. Kata Kunci: Maket, Membaca Petunjuk Denah, Kuantitatif Abstract: This research is motivated by the low ability to read floor plan instructions of fourth-grade students of SDN Karangjaya 01, Pebayuran District, Bekasi Regency. Students experience difficulties in navigating roads, understanding cardinal directions, determining locations, and interpreting symbols so that learning outcomes have not reached the Minimum Competency (KKM). This study aims to determine the effect of models (three-dimensional replicas) on floor plan reading abilities. This study uses a quantitative approach with a one-group pretest–posttest design. The subjects of the study were 30 fourth-grade students who were selected using a saturated sampling technique. The instrument used was a multiple-choice test whose validity and reliability have been tested. Data analysis used normality tests, homogeneity tests, paired sample t-tests, and N-Gain tests. The results showed that the average pretest score of 68.97 increased to 80.93 in the posttest, with a calculated t-value of 21.364 > t-table 2.042 (Sig. 0.000 < 0.05) and an N-Gain of 0.4629, categorized as moderate. Thus, mock-ups have a positive and significant effect on students' ability to read floor plan instructions. Keywords: Maket, Reading Floor Plan Instructions, Quantitative Abstrak: Penelitian ini dilatarbelakangi oleh rendahnya kemampuan membaca petunjuk denah peserta didik kelas IV SDN Karangjaya 01 Kecamatan Pebayuran Kabupaten Bekasi. Peserta didik mengalami kesulitan menelusuri jalan, memahami arah mata angin, menentukan lokasi, dan menafsirkan simbol sehingga hasil belajar belum mencapai KKM. Penelitian ini bertujuan mengetahui pengaruh media maket (tiruan tiga dimensi) terhadap kemampuan membaca denah. Penelitian menggunakan pendekatan kuantitatif dengan desain one group pretest–posttest. Subjek berjumlah 30 peserta didik kelas IV yang diambil dengan teknik sampling jenuh. Instrumen berupa tes pilihan ganda yang diuji validitas dan reliabilitasnya. Analisis data menggunakan uji normalitas, homogenitas, paired sample t-test, dan N-Gain. Hasil penelitian menunjukkan rata-rata nilai pretest 68,97 meningkat menjadi 80,93 pada posttest dengan thitung 21,364 > ttabel 2,042 (Sig. 0,000 < 0,05) serta N-Gain 0,4629 kategori sedang. Dengan demikian, maket berpengaruh positif dan signifikan terhadap kemampuan membaca petunjuk denah peserta didik. Kata Kunci: Maket, Membaca Petunjuk Denah, Kuantitatif.